THE AUDIT OF SUBSEQUENT EVENTS: AN ANALYSIS OF ITS IMPORTANCE FROM THE VIEW OF INDEPENDENT AUDITORS ACTING IN BRAZILIAN OPEN CAPITAL COMPANIES - Mucillo, Fernanda Mazzaro (2022)
The present study investigates the importance that Brazilian independent auditors working at B3 (Brasil, Bolsa, Balcão) attach to subsequent events. For this purpose, we divided the second-order latent variable “importance” into three subgroups that form the research construct: the importance of the information generated; the importance of evidence-seeking procedures before the issuance of the audit report; and the importance of evidence-seeking procedures after the issuance of the audit report and publication of the financial statements. The data collection of this quantitative, descriptive and survey took place in the first half of 2018, the final sample had 74 participants (21.08% of the population), and the answers were analyzed with the help of the R Development Core Team statistical environment, using the Structural Equations Model (SEM) to handle the data. The research contributes by verifying the levels of importance attributed by auditors in the audit work of subsequent events, thus visualizing their relationship with the service provided. The results show that the Brazilian independent auditors consider the information generated and the procedures for searching for subsequent events important, except when the generated information changes only one account of the financial statements (low relevance). Another finding of the research was that, between meeting the deadlines and issuing quality information, the evidence found in the study indicates that auditors prefer to comply with legal deadlines. The research also sought to analyze if professional characteristics influence the level of information they attribute to subsequent events. In this sense, we identified that the experience time, the level of effort involved in the audit procedures, and the difficulties in the search processes positively influence the importance of the factor performed procedures.